Effects of U.K. direct investment overseas : final report - Reddaway, William Brian; Potter, S. J.; Taylor, C. T. (London : Cambridge U.P., 1968)
The book contains the final report of United Kingdom direct overseas investment on the British balance of payments.
Includes index
usc 17/07/18
Loans
Keywords: Investments, British